Qualitative and quantitative analysis of agar in edible bird's nest and related products based on a daughter oligosaccharide-marker approach using LC-QTOF-MS. (February 2022) - Cheng, Hui-Yuan; Li, Li-Feng; Wu, Wen-Jie; Zhang, Quan-Wei; Liu, Man; Wong, Tin-Long; Kong, Hau-Yee; Lai, Cheuk-Hei; Bao, Wan-Rong; Huo, Chu-Ying; Zheng, Hong-Ming; Hou, Qiu-Ke; et al.
Abstract: Agar is a common adulterant of edible bird's nest (EBN) and is often added in preparation of EBN products. Currently, there is no method that can be used to assess agar content in products because it is difficult to analyze a macromolecule that does not absorb UV. Herein, we report an efficient qualitative and quantitative method for detecting agar in food products based on a daughter oligosaccharide-marker approach. There are three steps: 1) acid hydrolysis of parent agar to release daughter oligosaccharides, 2) p-aminobenzoic ethyl ester (ABEE) labeling, 3) Liquid Chromatography Quadrupole Time-of-Flight Mass Spectrometry (LC-QTOF-MS) analysis. Twenty-four daughter oligosaccharides found to be specific to agar were selected as qualitative authentication markers. One of them, which showed high signal abundance and satisfactory linearity with standard agar, was selected as the assay marker; and it was identified as neoagarotetraose by comparing with standard references. Based on this marker, a qualitative and quantitative analytical method was successfully developed and well-validated in terms of linearity, precision, repeatability, and accuracy. This method revealed that agar is being used as a minor adulterant (one out of 12) in EBN raw material. In this study, 60% of commercial "agar" was, in fact, starch and a significant number of EBN products labeled as having agar either did not contain agar or did not contain the amount listed on the label. It is proved that this oligomer approach can be used to improve quality control of all commercial products labeled as or containing agar. Furthermore, this oligomer approach is efficient and reliable in the quality analysis of other polymers like agar. Highlights: An oligosaccharide marker approach to analyze the agar quality was established. Twenty-four qualitative and one quantitative authentication marker were found. The quantitative authentication marker was identified to be neoagarotetraose. This method revealed the quality mess of agar and related EBN products.